Correcting parentage relationships in the endangered California Condor: Improving mean kinship estimates for conservation management. Issue 3 (8th May 2021) - Moran, Brigid M; Thomas, Steven M; Judson, Jessica M; Navarro, Asako; Davis, Heidi; Sidak-Loftis, Lindsay; Korody, Marisa; Mace, Michael; Ralls, Katherine; Callicrate, Taylor; Ryder, Oliver A; Chemnick, Leona G; et al.
Abstract: Maintaining the existing biodiversity of endangered species is a goal of conservation management programs, and a major component of many collaborative efforts undertaken by zoos, field biologists, and conservation scientists. Over the past 3 decades, the San Diego Zoo has performed long-term genetic studies in support of the recovery program for the critically endangered California Condor ( Gymnogyps californianus ). This work has included sex determination of hatchlings and parentage confirmation using microsatellite genotyping. This paper describes the genetic work associated with the California Condor recovery program, which aims to provide a highly accurate pedigree for making informed captive pairing and release recommendations. Initial genotyping began after reintroduced California Condors started reproducing, and the focus was on birds hatched from their wild-laid eggs. However, genetic analysis showed discrepancies relative to behavioral observations of wild birds and led to the species-wide testing of all available samples. This genetic study has resolved instances of individual misidentifications and parental misassignments, verified the first cases of extra-pair paternity in this species, identified parentage where chicks were observed being raised by trios, and found 2 apparent de novo mutations in the captive condor population. Correcting the California Condor pedigree according to genetic parental analysis has produced more accurate estimates of mean kinship values among living birds, ranking potential breeders according to their actual breeding value and helping managers to make informed decisions about captive pairing and release of condors in the wild. Lay Summary: In the past 30 years, the San Diego Zoo has genotyped 911 California Condors using 21 microsatellite markers to validate and determine parentage relationships of captive and wild birds. Parentage analyses have allowed us to resolve instances of misidentified individuals or parental misassignment and verify the first documented cases of extra-pair paternity in this species. Sex determination and parentage validation have supported the California Condor recovery program by correcting uncertainties and missing data in the pedigree. The corrected California Condor pedigree has allowed for more accurate estimates of mean kinship values in the living population, assisting decisions about the most suitable birds to be paired for breeding.